The Role of Psychological Qualities in the Process of the Formation of Sports Skill of Young Basketball Players - Anatoly Rovniy; Vladlena Pasko (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2018)
Purpose: to determine the level of the development of indices of the influence of the important psychological qualities and the personality characteristics that defines the effectiveness of the competitive activity of young basketball players in the process of sports skill. Material: the study involved basketball players of the first category and beginners athletes of the 2nd and 3rd categories. Research methods: analysis of scientific and methodological literature, interview of leading trainers, pedagogical observations, pedagogical experiment, pedagogical testing, psychological testing, methods of mathematical statistics. Results: Significant psychological qualities and personality characteristics are established which contribute to increasing the level of competitive activity. Conclusions: the conducted research contributed to increasing the importance in the optimal level of development and manifestation of psychological qualities and personality traits in enhancing athletic skill. As a result of the research important psychological qualities and personality traits are established that contribute to the increase in the level of competitive activity.